Penggunaan Pestisida Biorasional untuk Pengendalian Penyakit Hawar Daun Bakteri pada Tanaman Padi - Agus Nurawan; Yati Haryati; Kiki Kusyaeri Hamdani (Proceedings Series on Physical & Formal Sciences, 2021)
Bacterial leaf blight can cause rice loss between 15-80%. Biorational pesticides can be an alternative to controlling the disease. Bacillus firmus, Burkholderia sp, and Serratia marcescens against bacterial leaf blight on rice plants in the field. The study was conducted in Maret-Juni 2014 in the land of the Independent Farmers Group, Cipeuyeum Village, Haurwangi District, Cianjur Regency, West Java. The design uses a randomized complete block design (RCBD) with 6 treatments and 4 replications. The treatments consist of: 1) Mekongga + biorational, 2) Inpari 14 + biorational, 3) Sintanur + biorasional, 4) Mekongga + without biorational, 5) Inpari 14 + without biorational, and 6) Sintanur + without biorational. The results of the study showed that the application of biorational pesticides can reduce the intensity of bacterial leaf blight disease. Sintanur varieties with the application of biorational pesticides produce higher and higher R / C ratios of 6.81 tons ha-1 and 2.79.